Digital Innovation in Teacher Development: The Impact of the Platform Merdeka Mengajar on English Teachers’ Pedagogical Competence at MAN Pinrang - Rasdillah; Sunra, La; Korompot, Chairil Anwar (Har Press Indonesia, 2025)
This research aims (1) to find out the activities carried out by English teachers using Platform Merdeka Mengajar at MAN Pinrang to improve their pedagogical competence, and (2) to explore the perception of English teachers in using Platform Merdeka Mengajar at MAN Pinrang to improve their pedagogical competence. In this study, the researcher used a descriptive qualitative method. Three teachers who use Platform Merdeka Mengajar were selected as participants. Data were collected through observations and interviews. The results showed that there are several activities carried out by teachers in using Platform Merdeka Mengajar, namely in terms of developing lesson plans, improving self-development, using technology in the teaching process, and utilizing Platform Merdeka Mengajar features such as teaching tools (modules, teacher manuals student books), inspirational video, and portfolio evidence. Teachers utilize these features to find references in designing lesson plans and to find inspiration and creative learning methods. The perceptions of teachers using Platform Merdeka Mengajar to improve their competence are that teachers can easily access the various features provided. The available features are also beneficial in improving their competence by providing various references, such as modules and various best practice videos that can be used to adjust learning methods. This finding improves English teachers’ pedagogical competence, especially in adjusting learning methods and finding references. In addition, several obstacles are experienced in using Platform Merdeka Mengajar, such as the account used to access the platform being deleted and experiencing network constraints that are sometimes less stable. This shows the importance of improving infrastructure and technical management to maximize and ensure that the platform’s potential can be fully utilized to improve teachers’ pedagogical competence.